Pengaruh Konsentrasi Penambahan Ekstrak Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Terhadap Aktivitas Antioksidan Dan Sensoris Mayones - Al-Hakim, Muhammad Eriansyah; Puspawati, Gusti Ayu Kadek Diah; Putra, I Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 1 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i01.p08, 2024)
Mayonnaise is a processed product that commonly used as a dressing on a food such as salad or sandwiches. Oil is the main structure in making mayonnaise and easily oxidated that can spoil mayonnaise, commonly synthethic antioxidant is added to mayonnaise to prevent spoilage of mayonnaise. Synthetic antioxidants is known have a bad effects to human body compared to natural antioxidant, one of it are belimbing wuluh leaf extract,but extract concentration is need to be studied further. This research aimed to find out the effect of adding wuluh starfruit leaf extract on antioxidant activities and sensory of mayonnaise and determine the best concentration of belimbing wuluh extract. The research method used completely randomized design (CRD) with concentration addition consisting of five levels, 0%, 0,25%, 0,75%, and 1%. Each concentration is repeated three times to 15 experimental units. The data then analyzed using analysis of variance, if the treatment had a significant effect on the parameters, then continued with the Duncan Multiple Range Test (DMRT). The results showed that addition belimbing wuluh leaf extract in mayonnaise has significant effect in antioxidant activities, peroxides value, total phenolic content, water content, and color test L*,a*, b*, The best addition of belimbing wuluh leaf extract is at 1% concentration with 69,99% antioxidant activities, 111,27 mg GAE/g total phenolic content, 16,16 mg MDA/kg TBA values, 1344,4 meq peroxides/kg of peroxides values, water content at 11,8%, L* colour at 56,0, a* colours at -2,10, b* colours at 43,6, sensory characteristic color neutral, aroma neutral, texture neutral, flavor neutral, and overall acceptance neutral.